IMPLEMENTASI PELIMPAHAN KEWENANGAN TERHADAP PEMBERIAN PELAYANAN PERIZINAN DAN NON PERIZINAN PENANAMAN MODAL MENURUT UNDANG-UNDANG NO. 25 TAHUN 2007 TENTANG PENANAMAN MODAL (Studi di KEK Sei Mangkei Kab. Simalungun) - Tommy Aditia Sinulingga; Budiman Ginting; Sunarmi Sunarmi; Mahmul Siregar (USU LAW JOURNAL, 2018)
ABSTRACT Special economic zone (SEZ) in the objective services of licensing and non-standard licensing investment is done with one Integrated Service One Door System (PTSP). To facilitate the PTSP in SEZs granted to the Administrator of the SEZ. Based on the background of the research analyzed implementation delegation of authority towards the awarding service of licensing and non-standard licensing investments according to law No. 25 of 2007 about Investments with objects research done at Sei Mangkei SEZ Simalungun district. The SEZ Administrator  Sei Mangkei get delegation the authority of the BKPM with head rules BKPM No. 1 of 2014, head rules BKPM No. 2 of 2014, Minister of the Interior with Ministry of Home Affairs regulation No. 68/d. DAG/10/2014 revised Ministry of Home Affairs regulation No. 2 the year 2018, Governor with Governor’s regulation No. 4 of 2015, regent of regent’s regulation No. 35 of 2014. However, these functions are performed by the Administrator not optimal SEZ Sei Mangkei because he has yet to the delegate of authority to the Ministry of local government non-standard licensing about regional tax incentives, tax, customs and taxes, freight traffic, immigration, land tenure and licensing and non-standard licensing from ministries/related agencies specifically SEZ. It is the occurrence of disharmoni between the Central Government and regions cause bureaucratic services.   Keywords:    Delegate of authority, Licensing, Investment, The Special Economic Zone of Sei Mangkei.